Pelajaran bahasa Arab lengkap terjemah jami'ud duruusil 'Arabiyyah - Syaikh Mushthafa al Ghulayaini (Asy-Syifa', 1992)
ws.jl.2-3.c.1/tr, jil.1=c.1-2; jil, 3=c.2-3/ir, jil.3,c.4/ir, jil.1,c.3/tr, jil.1=c.4; jil.3=c.5/en, jil.2=c.2/en, jil.1=c.5/tr, jil.1=c.6; jil.2=c.3/nr,jil.3= .17